Precise strip for lithium battery explosion-proof sheet and processing technology of precise strip
Through multi-pass rolling, recrystallization annealing and point-shaped working roller rolling of stainless steel raw material steel strips for lithium battery explosion-proof plates, the problems of insufficient corrosion resistance, high temperature resistance and scratch resistance of traditional explosion-proof plates are solved, and higher corrosion resistance, high temperature resistance and scratch resistance are achieved, ensuring the safety performance of the battery.
Patent Information
- Application Number
- CN202411725617.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The corrosion resistance, high temperature resistance and scratch resistance of traditional lithium battery explosion-proof tablets are insufficient, and cannot meet the high requirements of new lithium batteries for the top cover explosion-proof tablets.
The stainless steel raw steel strip was subjected to multiple rolling and recrystallization annealing treatment, combined with point-shaped working rolling and ultrafine matte sandblasting treatment, and obtained precision strips with a thickness of 0.5 to 0.7 mm and a surface roughness Ra0.5 to 0.7 μm, and then the finished product recrystallization annealing treatment to form an ultra-large crystal grain structure.
It significantly improves the corrosion resistance, high temperature and scratch resistance of the explosion-proof plate, extends the service life, and ensures the safety performance of the battery and the stability of the explosion-proof mark.
Smart Images

Figure CN119634431A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of precision strip production, and in particular relates to a precision strip for lithium battery explosion-proof sheets and a processing technology thereof. Background Art
[0002] New lithium batteries such as cylindrical batteries, square batteries, and blade batteries have high energy density, strong fast charging, high safety, and long life, making them highly compatible with the needs of mid-to-high-end passenger cars for long battery life and ultra-fast charging. In the electric vehicle market, Tesla was the first to introduce large cylindrical lithium batteries, and BMW, Weilai, and others quickly followed suit. In terms of battery companies, Tesla, Panasonic, Yiwei Lithium Energy, CATL, BYD, and others are also actively deploying new lithium batteries such as cylindrical batteries, square batteries, and blade batteries in response to customer demand. Lithium battery structural parts mainly include: shell, top cover, etc., among which the top cover includes explosion-proof plates, sealing rings, connecting plates, steel caps, etc., which mainly play the role of transmitting energy, carrying electrolyte, protecting safety, and fixing supporting batteries.
[0003] With the development of lithium battery technology, the requirements for explosion-proof plates on the top cover are getting higher and higher. The explosion-proof plates of traditional pre-nickel-plated SPCC carbon steel / aluminum sheets have gradually exposed the following shortcomings: 1. SPCC carbon steel is not resistant to corrosion; 2. The melting point of aluminum sheet is lower than that of stainless steel and is not resistant to high temperature; 3. The surface roughness of pre-nickel-plated SPCC carbon steel / aluminum sheet is low and is not scratch-resistant. Therefore, it is necessary to develop a precision strip material for lithium battery explosion-proof plates with excellent corrosion resistance, high temperature resistance and scratch resistance and its processing technology. Summary of the invention
[0004] The main purpose of the present invention is to propose a precision strip material for lithium battery explosion-proof plates and a processing technology thereof, which can effectively solve the problems in the background technology.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] A processing technology for a precision strip for lithium battery explosion-proof sheets comprises the following steps:
[0007] S1. Raw material initial rolling: a stainless steel raw material strip with a thickness of 1.5 to 1.7 mm is used for 4 to 6 rolling passes, and the deformation of each of the last three rolling passes does not exceed 10%, and the rolling speed of each pass does not exceed 150 m / min, to obtain a medium billet steel strip with a thickness of 0.9 to 1.2 mm and a surface roughness of Ra 0.7 to 0.9 μm;
[0008] S2. Recrystallization annealing of the intermediate billet: The intermediate billet steel strip is subjected to recrystallization annealing in a continuous annealing furnace, with an annealing temperature of 950-1050°C and an annealing speed of 20-30 m / min, and high-concentration and high-flow hydrogen protection is used throughout the process;
[0009] S3, finished product finishing rolling: after the recrystallization annealing of the intermediate billet is completed, the intermediate billet steel strip is rolled for 4 to 6 times, the deformation of each rolling in the last two rolling passes does not exceed 10%, the rolling speed of each rolling pass does not exceed 150m / min, and the dot-shaped working rolls with a surface roughness of Ra1.0 to 1.5μm are replaced for each of the last two rolling passes to obtain a finished steel strip with a thickness of 0.5 to 0.7mm and a surface roughness of Ra0.5 to 0.7μm;
[0010] S4. Finished product recrystallization annealing: The finished steel strip undergoes recrystallization annealing in a continuous annealing furnace at a temperature of 1100-1150°C and an annealing speed of 10-20 m / min. High-concentration, high-flow hydrogen protection is used throughout the process.
[0011] Preferably, in step S1, the stainless steel raw material steel strip is stainless steel with Nb element Nb≥0.4% added.
[0012] Preferably, in step S3, the width of the dot-shaped working roller is 700-1400 mm, the diameter is 45-55 mm, and the surface is subjected to ultra-fine matte sandblasting treatment.
[0013] Preferably, in step S4, during the recrystallization annealing process, the holding temperature is greater than 1100° C. and the holding time is greater than 3 minutes.
[0014] A precision strip material for lithium battery explosion-proof pieces, the precision strip material for lithium battery explosion-proof pieces is produced by the above-mentioned processing technology.
[0015] The present invention provides a precision strip material for lithium battery explosion-proof sheets and a processing technology thereof, which has the following beneficial effects:
[0016] 1. The raw material steel strip of the present invention adopts stainless steel, so that the explosion-proof plate obtained subsequently has excellent corrosion resistance and high temperature resistance. In the present invention, the stainless steel raw material steel strip specifically adopts stainless steel with Nb element Nb≥0.4% added to improve the pitting corrosion resistance of the steel strip, further improve the corrosion resistance of the explosion-proof plate, and extend the service life.
[0017] 2. In the finishing rolling of finished products, in order to obtain higher precision of surface roughness, the last two rolling passes are rolled with special dotted working rolls with surface roughness Ra1.0~1.5μm, so that the surface roughness of the steel strip reaches Ra0.5~0.7μm, which can significantly improve the scratch resistance of the explosion-proof plate, and at the same time improve the welding bonding strength between the explosion-proof plate and the external connecting parts, ensuring the safety performance of the battery.
[0018] 3. After the recrystallization annealing of the finished product is completed, the finished steel strip of the present invention obtains low hardness and ultra-large grains, and the average grain size is ≤6 levels, which can ensure the explosion-proof plate's requirements for the residual thickness of the explosion-proof scoring line, and the residual thickness is stably greater than 0.05mm, thereby ensuring that the explosion-proof plate still has sufficient thickness after scoring processing to withstand the internal pressure and prevent premature rupture. At the same time, it also ensures that it can reliably rupture to release pressure under the designed pressure threshold, thereby ensuring the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a flow chart of the processing technology of the present invention;
[0020] Figure 2 This is a graph showing the surface roughness Ra test results of Example 1 of the present invention;
[0021] Figure 3 This is a graph showing the average grain size test results of Example 1 of the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clear, the technical solutions of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention.
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0025] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "multiple" means two or more, unless otherwise clearly and specifically defined. In addition, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0026] Reference Figure 1 , a processing technology for a precision strip for lithium battery explosion-proof sheets, comprising the following steps:
[0027] S1. Raw material initial rolling: Use stainless steel raw material steel strip with a thickness of 1.5-1.7 mm and roll it through 4-6 passes. The deformation of each of the last three passes does not exceed 10%, and the rolling speed of each pass does not exceed 150m / min to obtain a medium-sized steel strip with a thickness of 0.9-1.2mm and a surface roughness of Ra0.7-0.9μm.
[0028] The raw material steel strip is made of stainless steel, so that the explosion-proof plate produced subsequently has excellent corrosion resistance and high temperature resistance. In the present invention, the stainless steel raw material steel strip specifically adopts stainless steel with Nb element Nb≥0.4% added. Niobium is a strong carbide-forming element that can combine with carbon to form stable carbides, thereby reducing the precipitation of carbides at the grain boundaries and improving the pitting corrosion resistance of the steel strip. The improvement of pitting corrosion resistance means that the performance of the material in a local corrosion environment is enhanced, which can further improve the corrosion resistance of the explosion-proof plate and extend its service life.
[0029] The thickness of the intermediate steel strip is 0.9-1.2 mm, which is achieved by multiple rolling passes, and the surface roughness Ra 0.7-0.9 μm is obtained by the last three rolling passes. Therefore, the deformation of each of the last three rolling passes is controlled not to exceed 10%, and the rolling speed of each pass is controlled not to exceed 150 m / min to ensure the surface roughness accuracy of the intermediate steel strip.
[0030] S2. Recrystallization annealing of the intermediate billet: The intermediate billet steel strip is subjected to recrystallization annealing in a continuous annealing furnace, with an annealing temperature of 950-1050°C and an annealing speed of 20-30 m / min, and high-concentration and high-flow hydrogen protection is used throughout the process;
[0031] Through high-temperature annealing treatment, the alloy elements in the steel strip are fully dissolved, the internal stress generated during the rolling process is eliminated, the microstructure of the material is improved, and the plasticity and toughness of the steel strip are improved. At the same time, the use of hydrogen protection can prevent the steel strip from oxidation and maintain the purity of the material.
[0032] S3, finished product finishing rolling: after the recrystallization annealing of the intermediate billet is completed, the intermediate billet steel strip is rolled through 4 to 6 passes, the deformation of each of the last two rolling passes does not exceed 10%, the rolling speed of each pass does not exceed 150m / min, and the dot-shaped working rolls with a surface roughness of Ra1.0 to 1.5μm are replaced for each of the last two rolling passes to obtain a finished steel strip with a thickness of 0.5 to 0.7mm and a surface roughness of Ra0.5 to 0.7μm.
[0033] Preferably, the dot-shaped working roller has a width of 700-1400 mm, a diameter of 45-55 mm, and a surface treated with ultra-fine matte sandblasting.
[0034] After multiple rolling passes, the thickness of the steel strip is further reduced to 0.5-0.7 mm. In order to obtain a higher precision of surface roughness, the last two rolling passes are rolled with special dotted working rolls with a surface roughness of Ra1.0-1.5 μm, so that the surface roughness of the steel strip reaches Ra0.5-0.7 μm, which can significantly improve the scratch resistance of the explosion-proof plate, while improving the welding bonding strength between the explosion-proof plate and the external connector, ensuring the safety performance of the battery.
[0035] S4. Finished product recrystallization annealing: The finished steel strip undergoes recrystallization annealing in a continuous annealing furnace at a temperature of 1050-1100°C and an annealing speed of 10-20 m / min. High-concentration, high-flow hydrogen protection is used throughout the process.
[0036] Preferably, during the recrystallization annealing process, the holding temperature is greater than 1100° C. and the holding time is greater than 3 minutes.
[0037] After the finished product recrystallization annealing is completed, the hardness of the finished steel strip will decrease, which is helpful for the subsequent punching and production of explosion-proof disks. At the same time, the finished product recrystallization annealing promotes the growth of grains to form an ultra-large grain structure. Under the above-mentioned precise finished product recrystallization annealing parameters, the finished steel strip can achieve an average grain size of ≤6 levels (the smaller the level, the coarser the grains), which helps to improve the plasticity and toughness of the explosion-proof disk.
[0038] In the application of lithium battery explosion-proof plates, the explosion-proof score line is a structure designed to rupture and release pressure when the internal pressure of the battery is too high. The residual thickness of the explosion-proof score line is an important parameter in the design of lithium battery explosion-proof plates, which directly affects the safety performance of the battery.
[0039] When the hardness of the explosion-proof disk is higher, greater force is required to reach the same depth during the scoring process, which may result in a smaller residual thickness. On the contrary, materials with lower hardness are more likely to undergo plastic deformation during scoring, which may leave a larger residual thickness. Plastic toughness refers to the ability of a material to undergo plastic deformation without breaking when subjected to external force. Explosion-proof disks with good plastic toughness can better absorb impact force during the scoring process, reduce the generation of cracks, and thus maintain a larger residual thickness.
[0040] After the finished product is recrystallized and annealed, the finished steel strip has low hardness and super-large grains, and the average grain size is ≤6 levels, which can ensure the explosion-proof plate's requirement for the residual thickness of the explosion-proof scoring line, and the residual thickness is stably greater than 0.05mm, thereby ensuring that the explosion-proof plate still has sufficient thickness to withstand the internal pressure after scoring processing to prevent premature rupture, and also ensuring that it can reliably rupture to release pressure under the designed pressure threshold, thereby ensuring the safety performance of the battery.
[0041] Example 1
[0042] S1. Raw material initial rolling: Use a stainless steel raw material steel strip with a thickness of 1.5 mm and undergo 4 rolling passes. The deformation of each of the last three rolling passes does not exceed 20%, and the rolling speed of each pass does not exceed 150 m / min, to obtain a medium-sized steel strip with a thickness of 0.9 mm and a surface roughness of Ra0.78 μm.
[0043] S2. Recrystallization annealing of the intermediate billet: The intermediate billet steel strip is subjected to recrystallization annealing treatment in a continuous annealing furnace at a temperature of 950°C and an annealing speed of 30 m / min. High-concentration and high-flow hydrogen protection is used throughout the process, and the concentration of the hydrogen protection gas can reach 99.99%.
[0044] S3, finished product finishing rolling: after the recrystallization annealing of the intermediate billet is completed, the intermediate billet steel strip is rolled through 4 passes, the deformation of each of the last two rolling passes does not exceed 10%, the rolling speed of each pass does not exceed 150m / min, and the dot-shaped working rolls with a surface roughness of Ra1.0 are replaced for each of the last two rolling passes to obtain a finished steel strip with a thickness of 0.5mm and a surface roughness of Ra0.587μm.
[0045] S4. Finished product recrystallization annealing: The finished steel strip undergoes recrystallization annealing in a continuous annealing furnace at a temperature of 1100°C and an annealing speed of 20m / min. High-concentration and high-flow hydrogen protection is used throughout the process, and the concentration of the hydrogen protection gas can reach 99.99%.
[0046] Reference Figure 2 , Figure 3 The finished steel strip produced by the above processing technology has a surface roughness of Ra0.587μm (measured by a desktop roughness meter) and an average grain size of 5.5.
[0047] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A processing technology for precision strips for lithium battery explosion-proof sheets, characterized in that: The following steps are involved: S1. Raw material initial rolling: a stainless steel raw material strip with a thickness of 1.5 to 1.7 mm is used for 4 to 6 rolling passes, and the deformation of each of the last three rolling passes does not exceed 10%, and the rolling speed of each pass does not exceed 150 m / min, to obtain a medium billet steel strip with a thickness of 0.9 to 1.2 mm and a surface roughness of Ra 0.7 to 0.9 μm; S2. Recrystallization annealing of the intermediate billet: The intermediate billet steel strip is subjected to recrystallization annealing in a continuous annealing furnace, with an annealing temperature of 950-1050°C and an annealing speed of 20-30 m / min, and high-concentration and high-flow hydrogen protection is used throughout the process; S3, finished product finishing rolling: after the recrystallization annealing of the intermediate billet is completed, the intermediate billet steel strip is rolled for 4 to 6 times, the deformation of each rolling in the last two rolling passes does not exceed 10%, the rolling speed of each rolling pass does not exceed 150m / min, and the dot-shaped working rolls with a surface roughness of Ra1.0 to 1.5μm are replaced for each of the last two rolling passes to obtain a finished steel strip with a thickness of 0.5 to 0.7mm and a surface roughness of Ra0.5 to 0.7μm; S4. Finished product recrystallization annealing: The finished steel strip undergoes recrystallization annealing in a continuous annealing furnace at a temperature of 1100-1150°C and an annealing speed of 10-20 m / min. High-concentration, high-flow hydrogen protection is used throughout the process.
2. The processing technology of the precision strip for lithium battery explosion-proof sheet according to claim 1, characterized in that: In step S1, the stainless steel raw material steel strip is specifically made of stainless steel with Nb element Nb≥0.4% added.
3. The processing technology of the precision strip for lithium battery explosion-proof sheet according to claim 1 is characterized in that: In step S3, the width of the dotted working roll is 700-1400 mm, the diameter is 45-55 mm, and the surface is subjected to ultra-fine matte sandblasting treatment.
4. The processing technology of the precision strip for lithium battery explosion-proof sheet according to claim 1 is characterized in that: In step S4, during the recrystallization annealing process, the holding temperature is greater than 1100° C. and the holding time is greater than 3 minutes.
5. A precision strip for lithium battery explosion-proof sheet, characterized in that: The precision strip material for lithium battery explosion-proof sheets is produced by the processing technology described in any one of claims 1 to 4.
Citation Information
Patent Citations
8B cold-rolling precision steel belt and manufacturing method thereof
CN105195510A
Stainless steel precision strip for automobile decoration strip and processing technology of stainless steel precision strip
CN114147064A
Production process of textured surface of stainless steel band for gearbox friction plate
CN115709220A
Processing method for improving contact resistivity of precise strip steel base material of bipolar plate
CN116786584A
Method for solving roll sticking mark defect during finish rolling of thin-gauge 316-series stainless steel
CN116900045A